Effect of pH variation on Bandgap and Visible Light Photocatalytic Properties of TiO2 Nanoparticles - Sarathi R; Meenakshi Sundar S (Journal of Water and Environmental Nanotechnology, 2022)
Titanium-di-oxide nanoparticles are synthesized via a microwave-assisted solvothermal route for different pH values. The effect of the acidic and basic nature of the solvent due to the pH value is reflected in the crystalline size of the compound. The purpose of this work is to synthesize Titanium dioxide nanoparticles and to observe their application in degrading industrially contaminated water using normal tap water. The crystalline sizes are calculated using XRD analysis and confirmed with HRTEM. The chemical composition and oxidation state are confirmed with XPS studies. Optical properties are carried out with UV-Vis, FTIR, and PL spectra. Photocatalytic studies are carried out to degrade the dye in industrial water. The efficiency of degradation is calculated with the UV-Vis data and formula. The reduction in band gap and high permanence has greatly supported in making it acceptable for photocatalytic activity under visible light. Dependence of time, initial dye concentration, and pH of the dye solution on TiO2 as a catalyst is investigated under the illumination of a visible lamp, and degradation efficiency to the highest of 96.79% has been obtained.